Il lungo dopoguerra freddo: la crisi del multilateralismo e la ricerca di nuovi equilibri geopolitici - Pietro Sebastiani (Democrazia e Diritti Sociali, 2022)
The essay analyses the evolution of the national and international scene between the Twentieth and the Twenty-first century to reach our days, plagued by the pandemic from Covid-19 and the war in Ukraine. The Author dwells on the need to rebuild a new multilateral architecture at the international level to effectively address cross-cutting problems, such as poverty, health, work and the protection of the Earth from pollution.